Rajah dan Spiritualitas Lokal dalam Hukum Islam; Studi Analisis Tafsir Hermeneutik - Drajat, Amroini; Mustapa; Warnisyah Harahap, Elly (Jurisprudensi: Jurnal Ilmu Syariah, Perundang-Undangan dan Ekonomi Islam, 2024)
This study examines the integration of rajah (spiritual chants or incantations) and local spirituality within the context of Islamic law through a hermeneutic interpretative analysis. The research explores how local spiritual practices, particularly the use of rajah, coexist and interact with the principles of Islamic jurisprudence. By employing a hermeneutic approach, the study aims to uncover the deeper meanings and implications of rajah in relation to the spiritual and legal frameworks of Islam. It investigates the cultural and historical significance of rajah, its acceptance and adaptation within various Islamic communities, and the interpretative challenges it presents. The findings reveal a complex interplay between local traditions and Islamic legal thought, highlighting the dynamic nature of religious interpretation and the need for contextual understanding in the application of Islamic law. This study contributes to a broader comprehension of how local spiritual practices can be harmonized with Islamic jurisprudence, offering insights into the evolving relationship between tradition and religion.